Maternal perinatal anxiety and neural responding to infant affective signals: Insights, challenges, and a road map for neuroimaging research. (December 2021) - Yatziv, Tal; Vancor, Emily A.; Bunderson, Madison; Rutherford, Helena J.V.
Highlights: Anxiety symptoms are prevalent among women in the prenatal and postnatal periods. This review focuses on how anxiety modulates neural responses to infant cues. Anxiety modulates detection, interpretation, or regulation, depending on valence. Limitations include inconsistent methodologies and consideration of depression. Future work should incorporate cognition and behavior for multiple analysis levels. Abstract: Anxiety symptoms are common among women during pregnancy and the postpartum period, potentially having detrimental effects on both mother and child's well-being. Perinatal maternal anxiety interferes with a core facet of adaptive caregiving: mothers' sensitive responsiveness to infant affective communicative 'cues.' This review summarizes the current research on the neural correlates of maternal processing of infant cues in the presence of perinatal anxiety, outlines its limitations, and offers next steps to advance future research. Functional neuroimaging studies examining the neural circuitry involved in, and electrophysiological studies examining the temporal dynamics of, processing infant cues during pregnancy and postpartum are reviewed. Studies have generally indicated mixed findings, although emerging themes suggest that anxiety may be implicated in several stages of processing infant cues— detection, interpretation, and reaction— contingent upon cue valence. Limitations include inconsistent designs, lack of differentiation between anxiety and depression symptoms, and limited consideration of parenting-specific (versus domain-general) anxiety. Future studies should incorporate longitudinal investigation of multiple levels of analysis spanning neural, cognitive, and observed aspects of sensitive caregiving.